2002
DOI: 10.1002/ijc.10390
|View full text |Cite
|
Sign up to set email alerts
|

Basigin (cd147) is expressed on melanoma cells and induces tumor cell invasion by stimulating production of matrix metalloproteinases by fibroblasts

Abstract: Key words: basigin (CD147); malignant melanoma; invasion; metastasis; matrix metalloproteinaseBasigin (CD147), a transmembrane glycoprotein belonging to the Ig superfamily, was cloned from F9 embryonic carcinoma cells. 1 The Ig domain has strong homology with both the Ig variable domain and the major histocompatibility complex class II ␤ chain. It is expressed in various embryonic and adult tissues. 1,2 Because of its broad distribution, it was expected that basigin plays fundamental roles in various physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
214
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(234 citation statements)
references
References 46 publications
14
214
1
5
Order By: Relevance
“…The result is increased production of factors that participate in tumor virulence by promoting, for example, angiogenesis and degradation of the extracellular matrix. 5,28 Our finding of increased matrix metalloproteinase-2 staining in tumor cells near the inflammatory infiltrate is consistent with the literature and suggests that matrix metalloproteinase-2 may interact with the inflammatory infiltrate to further cutaneous squamous cell carcinoma progression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result is increased production of factors that participate in tumor virulence by promoting, for example, angiogenesis and degradation of the extracellular matrix. 5,28 Our finding of increased matrix metalloproteinase-2 staining in tumor cells near the inflammatory infiltrate is consistent with the literature and suggests that matrix metalloproteinase-2 may interact with the inflammatory infiltrate to further cutaneous squamous cell carcinoma progression.…”
Section: Discussionsupporting
confidence: 90%
“…Gelatinases, particularly gelatinase A (matrix metalloproteinase-2), demonstrate degradative activity against components of the basement membrane and may be involved in the progression of in situ lesions. 4,5 Matrix metalloproteinase-2 has affinity for gelatin; collagen I, IV, VII, X; tenascin; fibrillin; osteonectin; fibronectin; and monocyte chemoattractant protein 3. 1 Collagenase IV activity is particularly associated with basement membrane compromise.…”
mentioning
confidence: 99%
“…However, conflicting results regarding the putative involvement of EMMPRIN in the progression of melanomas were reported, implying that a more detailed analysis of EMMPRIN expression in human melanomas need to be conducted. 36,37 Our findings showed that many malignant tumors with a high incidence of EMMPRIN expression, such as, for example, head and neck SCCs or glioblastomas, are known to frequently overexpress EGFR, 38,39 suggesting that there might be a functional link between these 2 cell surface receptors. Indeed, evidence was provided that in immortalized NS2T2A1 breast cells EMMPRIN expression is induced by activation of EGFR through its ligand amphiregulin.…”
Section: Discussionmentioning
confidence: 70%
“…CD147 expression is elevated on several human tumors and has been correlated with the malignancy in some cancers such as primary breast cancer and ovarian cancer, etc. (7)(8)(9)(10)(11)(12). Despite the close correlation between CD147 expression and malignancy of some tumors, it is not clear whether CD147 has a functional role in tumor genesis and hepatocellular carcinoma (HCC) progression.…”
Section: Introductionmentioning
confidence: 99%